Indigenous Leadership of the Anglican Diocese of Accra, 1968 – 2012. - Quaye, D.N.A. (University of Ghana, 2014)
The Anglican Diocese of Accra (ADOA) has been confronted with the exodus of members from the church. From the time of the first indigenous bishop, various synods of the church have viewed it as a major problem. This tendency was attributed to the nature of the liturgy and the extensive way of worship. The liturgy even though repackaged and the worship style changed with the infusion of local instruments and choruses that meet the worship needs of the present generation, the anticipated result which led to the changes is yet to be realized by the church. This study focuses on the indigenous leadership of the ADOA. It covers the period 1968 – 2012. The thesis investigates the various activities, strategies and policies that characterized the running of the church first, by the western leadership before the indigenous leadership. The objective is to unveil the contribution of the local people and the challenges they faced in the management, leadership and above all the development of the church in the Greater Accra Region. The methods employed in this work are the historical and phenomenological approach. The historical method is used to recount the history of the origin of the Ga people, the introduction and development of Anglicanism in the Gold Coast, now Ghana. This includes antecedents to the leadership of the indigenous people in the ADOA, leadership by the indigenes and the process of indigenization. The phenomenological method is used at naming, describing and objectivity in data collection and analysis. These are then described from the perspectives of the respondents, that is, using peoples experience to give an objective description of it. The tools used for collating data were interview, discussion and questionnaire. Consequently, purposive sampling method was used to collect information from bishops, priests, lay faithful and church groups in the ADOA. The findings indicated that, in spite of the indigenous effort in the ADOA, in terms of the liturgy and worship, the church continues to be glued to the western style of worship and it has been difficult for the church to develop an entirely indigenous liturgy that will motivate and enhance the spirituality of parishioners as well as attract visitors which will aid its growth. Again the church continues to use the 1662 prayer book even under the indigenous leadership. Also the adaptation to the use of the English language at services and other religious gatherings is about (85%) and this is a major setback in the church. Information shows, the use of the English language scares even the semi-literate to be involved in the affairs of the church. Despite these challenges, the church managed to survive to date. The study therefore provides recommendations for creating good fortunes for the church and its members. It is believed that the research will be able to facilitate the desire of the church to overcome her current slow growth. In the final analysis, the findings will be useful to academia and also help the ADOA better understand the exodus of members in order to present the whole counsel of God with clarity, whilst maintaining the cultural heritage of the Ga people.
Thesis (MPhil) - University of Ghana, 2014